2018
DOI: 10.2340/16501977-2379
|View full text |Cite
|
Sign up to set email alerts
|

Combined transcranial direct current stimulation and breathing-controlled electrical stimulation for management of neuropathic pain after spinal cord injury

Abstract: The immediate analgesic effect of breathing-controlled electrical stimulation was confirmed. However, this effect was not augmented after one session of transcranial direct current stimulation treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
(79 reference statements)
0
8
0
Order By: Relevance
“…Over the last years, clinical studies targeting anodal M1 for pain control have had significant results. Different conditions have been considered as fibromyalgia [17,[48][49][50][51][52][53][54][55][56][57], neuropathic pain [58][59][60][61][62][63][64][65][66][67][68][69][70], migraine [71][72][73][74][75][76], low back pain (LBP) [77][78][79][80][81], musculoskeletal conditions [16,[82][83][84][85][86][87], myofascial pain syndrome [88,89], post-operative pain [90][91][92][93], among others (See Table 1).…”
Section: Primary Motor Cortex (M1) Tdcsmentioning
confidence: 99%
“…Over the last years, clinical studies targeting anodal M1 for pain control have had significant results. Different conditions have been considered as fibromyalgia [17,[48][49][50][51][52][53][54][55][56][57], neuropathic pain [58][59][60][61][62][63][64][65][66][67][68][69][70], migraine [71][72][73][74][75][76], low back pain (LBP) [77][78][79][80][81], musculoskeletal conditions [16,[82][83][84][85][86][87], myofascial pain syndrome [88,89], post-operative pain [90][91][92][93], among others (See Table 1).…”
Section: Primary Motor Cortex (M1) Tdcsmentioning
confidence: 99%
“…It is a safe and non-invasive therapeutic method that changes cortex excitability according to the stimulation polarity, producing long-lasting effects (9). In addition, previous studies suggested the use of tDCS as an approach to enhance or "boost" physical therapy (10,11). A commonly used form of rehabilitation is mirror therapy (MT), which involves a mirror being placed in a position that allows the patient to view a reflection of a body part (12).…”
Section: Introductionmentioning
confidence: 99%
“…We read with interest the article by Li et al on the use of combined transcranial direct current stimulation (tDCS) and breathing-controlled electrical stimulation (Bre-Estim) for management of neuropathic pain after spinal cord injury (1,2).…”
Section: Commentary On: "Combined Transcranial Direct Current Stimulamentioning
confidence: 99%
“…The authors did not specify the time interval between interventions, and why the pain level was assessed after 10 mins. In order to check the immediate effect the pain level should have been assessed immediately after the intervention (1).…”
Section: Commentary On: "Combined Transcranial Direct Current Stimulamentioning
confidence: 99%
See 1 more Smart Citation